Kinetics of the oxidation of oils derived from Peruvian foods rich in ω-3 and ω-6 fatty acids using the Rancimat method - Villanueva López, Eudes (2023)
Peru has several foods with high lipid content (especially oils), rich in omega fatty acids (ω-3 and ω-6) that are widely studied for their anti-inflammatory (ω-3) and pro-inflammatory (ω-6) effects. However, ω-3 and ω-6 are susceptible to oxidation resulting in accelerated deterioration of the oils. The objective of this work was to determine the oxidative stability index (OSI) of vegetable (seeds) and animal (anchoveta) oils from Peru, with high ω-3 and ω-6 contents, in order to compare oxidation kinetic parameters and shelf life. For this purpose, the Rancimat accelerated oxidation method was used, whose working parameters were: air flow (F = 25 L/h), sample weight (M = 3 g) and temperature range (T = 60-140 °C). The results indicated that the OSI values, as well as the shelf-life projection (T = 25°C) were in the following order: olive oil > chestnut > sesame > sacha inchi > flaxseed > chia > fish. The kinetic parameters of rate constant (k), activation energy (Ea), enthalpy (∆H), entropy (∆S) and temperature acceleration factor (Q10) varied significantly among the oils (p < 0.05). The comparison of the kinetic behavior of the studied samples is key for the development of new products with longer shelf life and increased nutritional value.